MAKNA SIMBOLIK RANDAI SEBAGAI KESENIAN MASYARAKAT MINANGKABAU DI KOTA PAYAKUMBUH PROVINSI SUMATERA BARAT - Putri, Deria Pradana; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Randai is one of traditional culture of Minangkabau people. There are symbolic aspect in art of randai with special meaning that is represented by clothing, musical instruments in art of randai, movements in randai. The purpose of this research was detemining the meaning of symbolic situation, the product of social interaction, and the interpretative of randai as art of Minangkabau people in Payakumbuh City.This research used qualitative methode by simbolic interaction approach. Informan of this research is randai’s trainer, randai’s playeras well as the figure of Minangkabau society who were selected by using purposive technique, and society in Payakumbuh City were selected by using accidental technique. Data collection technique used observation, interview and documentation.The result of research showed that symbolik situation meaning of randai as art of Minangkabau society in Payakumbuh City include physical objects such as costumes (Minangkabau costumes) and musical instrument in randai (Saluang, talempong, gandang, and bansi) with special meaning in every part while the social objects from art of randai include the movements of randai’s players (galombang dance and pencak silat), song on art of randai and social object based the message of randai which also has special meaning. The meaning of social product’s interaction includes the meaning of randai from the players’ side where the players interpret randai has culture and self protection’s value, from the trainer’s side randai has culture, religion, custom and art value, from the figure of Minangkabau people’s side randai has culture, history, unifying tool, custom, education, religion and art value and from Minangkabau people’s side randai has culture and art value. Interpretation’s meaning of randai include the closed action and the opened action. The closed action include internal and external motivation of randai’s players, and both of pleasure and proud to be a part of randai. The opened action of randai’s players include the expression of all players and the attitude of randai’s players who were always compact and have a good teamwork.Keyword: Symbolic Meaning, Randai, Symbolic Situation, The Product of Social Interaction, Interpretation